A Gender-Based Analyses of Saudi Freshmen Perceptions Regarding English Language Teaching Effectiveness of Native and Non-Native English Language Teachers - Al-Malki, Eidhah Abdullah (European Scientific Journal, ESJ, 2020)
The study in hand is a gender-based comparative analyses of Saudi freshmen regarding the effectiveness of native and non-native English language teachers (NELTs & NNELTs hence after). Relevant research studies have been consulted to develop a questionnaire to generate data. Relevant steps have been followed to determine its face validity and reliability. It was a quantitative study and the participants responded to a two-point selfdeveloped questionnaire. Independent-samples T-test has been run to test the hypothesesset for this study and collect descriptive data to answer the research questions. The data have reported that female participants of this survey favored NNELTs more as compared to the male participants but the difference in their perceptions for majority of items in all three categories of the questionnaire was not statistically significant. Null hypotheses have been partially rejected as majority of the questionnaire items do not report statistically significant differences along gender lines. The results also reveal that the participants of this survey have preferred NELTsthe most for teaching and assessment skills, professional attitudes and professional skills. The results have also indicated that NNELTs have been favored in teaching and assessing grammar and reading, providing relaxed atmosphere, using innovative strategies, motivating their students to learn, behaving in a more responsible manner, responding to their students questions better, understanding their students’ learning difficulties, understanding their students’ learning styles and preparing their students for independent learning. The findings of this empirical survey seem to suggest that both groups of English language teachers have their own strengths which bear positive overbearing in effectiveness ELT.